2016
DOI: 10.1016/j.bbmt.2015.08.032
|View full text |Cite
|
Sign up to set email alerts
|

User-Centered Design Groups to Engage Patients and Caregivers with a Personalized Health Information Technology Tool

Abstract: Health information technology (IT) has opened exciting avenues for capturing, delivering and sharing data, and offers the potential to develop cost-effective, patient-focused applications. In recent years, there has been a proliferation of health IT applications such as outpatient portals. Rigorous evaluation is fundamental to ensure effectiveness and sustainability, as resistance to more widespread adoption of outpatient portals may be due to lack of user friendliness. Health IT applications that integrate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…The inclusion of qualitative interviews strengthens the study and will help to guide future development of the system and studies. User designed health systems have been shown to increase functionality, specificity and uptake [27].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of qualitative interviews strengthens the study and will help to guide future development of the system and studies. User designed health systems have been shown to increase functionality, specificity and uptake [27].…”
Section: Discussionmentioning
confidence: 99%
“…Patients and caregivers can take charge of health information, including tracking symptoms or scheduling medical appointments with health technology [9]. Over the last several years, researchers have begun to study the needs of supporting families of patients with chronic illness [2,6]. Although studies have demonstrated improved outcomes when families have a shared sense of responsibility [1,7], there remains paucity of data supporting interventions for pediatric patients and family caregivers in the outpatient setting.…”
Section: Background and Related Workmentioning
confidence: 99%
“…A paper prototype of a health information technology (HIT) tool, called "BMT Roadmap," was developed to meet these needs. We then took the important step in gaining end-user feedback of our paper-based prototype, getting feedback from patients and caregivers in the design of our HIT using both low-fidelity and high-fidelity prototypes (phase 2) [6].…”
Section: Introductionmentioning
confidence: 99%
“…These studies eventually led to the development of BMT Roadmap, a HIT tool delivered on a consumer-friendly tablet computer (Apple iPad, Cupertino, CA) that integrates patientspecific health information [7]. BMT Roadmap includes the following domains: (1) real-time laboratory results that families can view even before the clinical team; (2) medications, with plain language summaries of common toxicities, indications for use, and instructions for administration; (3) clinical trials in which the patient was enrolled accompanied by a 1-page plain language study summary; (4) healthcare provider directory with "yearbook-style" photos; (5) visual depiction of the trajectory of HCT or "Phases of Care" as patients progress through the inpatient hospitalization; and (6) interactive discharge checklist that incorporates educational videos to prepare families for discharge (eg, centralline care). Herein, we report the implementation of phase 3 of our research, a qualitative study based on semistructured interviews conducted in caregivers who used BMT Roadmap throughout the patients' hospitalization.…”
Section: Introductionmentioning
confidence: 99%